A density functional theory study on the Hexa-peri-hexabenzocoronene nanographene oxide. (May 2020) - Chang, Lan; Cui, Wei; Vahabi, Vahid
Abstract: We investigated the structural, energetic, and electronic properties of a Hexa- peri -hexabenzocoronene (HBC) nanographene oxide (NGO), using density functional theory calculations. We found that oxygen atom preferably adds to the rim C–C bonds with Gibbs free energy change (298 K and 1 atm) of about −40.3 kcal/mol, forming epoxide. After the epoxide formation, the gap of HBC is reduced considerably by about 17.2%, which increases the electrical conductivity, and the work function is raised slightly from 3.44 to 3.64 eV. We found that by increasing the number of epoxide rings, the adsorption energy per oxygen atom decreases slightly and the electrical conductivity is increased. The solubility of HBC is increased by oxidation in both the water and benzene solvents. An unusual solubility is reported for the nonpolar HBC molecule in the polar water. The solvation energy of HBC and NGO is about −6.3 and −8.0 kcal/mol in water, and −2.4 and −3.1 kcal/mol in benzene solvent, respectively. Highlights: An oxygen atom preferably adds to the rim C–C bonds of Hexa- peri -hexabenzocoronene (HBC). By epoxide formation, the gap of HBC is reduced considerably by about 17.2%. The electrical conductivity, and the work function is raised by epoxide formation. The HBC solubility is increased by oxidation in both the water and benzene solvents. An unusual solubility is reported for the nonpolar HBC molecule in the polar water.